Evolution of a Novel Antiviral Immune-Signaling Interaction by Partial-Gene Duplication. - Bryan Korithoski; Oralia Kolaczkowski; Krishanu Mukherjee; Reema Kola; Chandra Earl; Bryan Kolaczkowski (PLoS ONE, 2015)
The RIG-like receptors (RLRs) are related proteins that identify viral RNA in the cytoplasm and activate cellular immune responses, primarily through direct protein-protein interactions with the signal transducer, IPS1. Although it has been well established that the RLRs, RIG-I and MDA5, activate IPS1 through binding between the twin caspase activation and recruitment domains (CARDs) on the RLR and a homologous CARD on IPS1, it is less clear which specific RLR CARD(s) are required for this interaction, and almost nothing is known about how the RLR-IPS1 interaction evolved. In contrast to what has been observed in the presence of immune-modulating K63-linked polyubiquitin, here we show that-in the absence of ubiquitin-it is the first CARD domain of human RIG-I and MDA5 (CARD1) that binds directly to IPS1 CARD, and not the second (CARD2). Although the RLRs originated in the earliest animals, both the IPS1 gene and the twin-CARD domain architecture of RIG-I and MDA5 arose much later in the deuterostome lineage, probably through a series of tandem partial-gene duplication events facilitated by tight clustering of RLRs and IPS1 in the ancestral deuterostome genome. Functional differentiation of RIG-I CARD1 and CARD2 appears to have occurred early during this proliferation of RLR and related CARDs, potentially driven by adaptive coevolution between RIG-I CARD domains and IPS1 CARD. However, functional differentiation of MDA5 CARD1 and CARD2 occurred later. These results fit a general model in which duplications of protein-protein interaction domains into novel gene contexts could facilitate the expansion of signaling networks and suggest a potentially important role for functionally-linked gene clusters in generating novel immune-signaling pathways.